Belief in Black Magic Among the Young Adults: Does Personality and Religion Matters? (Journal of Asian Development Studies, 2025)
The objective of the study was to evaluate the relationship between belief in black magic and personality traits concerning religion, as well as to examine mean differences between Muslims and non-Muslims on this variable. Personality traits were operationalised as extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience. The study employed a cross-sectional correlational design and a convenience sampling technique to collect data from 84 participants (both males and females, including Muslims and non-Muslims) aged 18 to 30 years. Two instruments were utilised: the Black Magic Belief Scale and the Big Five Inventory (BFI). The correlational analysis revealed that only extroversion and openness had a positive and significant relationship with Belief in Black Magic. Further analysis revealed significant mean differences between Muslims and non-Muslims for scores on the Belief in Black Magic. The study concluded with comprehensive implications.